Pengaruh Laporan Keberlanjutan dan Kebijakan Dividen Terhadap Nilai Perusahaan Dengan Leverage sebagai Variabel Moderasi - Putri Pangesti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Achmad Yani Yogyakarta, 2025)
This study aims to analyze the effect of sustainability reports and dividend policy on firm value with leverage as a moderating variable in textile companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The research employs a quantitative approach using secondary data derived from annual reports, sustainability reports, and dividend policy information of the companies. Data were analyzed using panel data regression with the Random Effect Model and Moderated Regression Analysis (MRA). The results indicate that sustainability reporting has a positive and significant effect on firm value, whereas dividend policy shows a positive but not significant effect. Leverage does not significantly moderate the relationship between sustainability reporting or dividend policy and firm value. The Adjusted R² value of 0.359751 suggests that approximately 36% of the variation in firm value is explained by the independent variables, with the remaining 64% influenced by other factors. The findings highlight that firms consistently implementing sustainability reporting tend to achieve higher firm value due to enhanced social and environmental responsibility. In contrast, dividend policy does not significantly impact firm value, as investors appear to prioritize sustainability and long-term prospects over dividend payouts. Therefore, sustainability reporting plays a more dominant role than dividend policy in increasing firm value in the Indonesian textile sector. Keywords: Sustainability Report, Dividend Policy, Leverage, Firm Value